Positionspapier mit konkreten Handlungsempfehlungen* der DGAI und des BDA: ökologische Nachhaltigkeit in der Anästhesiologie und Intensivmedizin = Ecological sustainability in anaesthesiology and intensive care medicine: a DGAI and BDA position paper with specific recommendations - Schuster, Martin; Richter, H.; Pecher, S.; Koch, S.; Coburn, M. (Anästhesiologie & Intensivmedizin, 2020)
Ibis position paper with specific recommendations was commissioned by the DGAI and BDA executive committees in March 2020 and was compiled by the joint "Commission on Sustainability in Anaesthesiology". With the impending climate disaster in mind, the aim of this position paper is to delineate with which specific measures anaesthesiologists can contribute to a consistent and sustained reduction in CO2 emissions and minimise the negative ecological implications associated with the fields of anaesthesiology and intensive care medicine. The paper is divided into six sections and, on the basis of published literature, presents the currently available evidence on how anaesthesiologists can incorporate sustainability aspects in their professional sphere of influence. Special attention is directed towards the environmental effects of drugs used in anaesthesiology and intensive care and their impact on climate change. In that regard, the direct and potent greenhouse gas effects of volatile anaesthetics are emphasized. In consequence, specific recommendations are made on reducing the damaging effects of volatile anaesthetics on the climate. With regard to consumables, the increasing use of disposable single-use items is the subject of critical analysis, and the need to incorporate the carbon footprint in the selection of products is stressed. As waste has significant direct and indirect ecological effects, the 5R concept is used to show how waste can be avoided in both the operating theatre and intensive care unit without upsetting existing processes. In addition to these measures directly related to the field of anaesthesiology, this position paper addresses further areas of concern indirectly associated with the everyday professional role of the anaesthesiologist. As such, the paper alludes to the significance of sustainable mobility with regard to everyday commutes, patient transfers, and conferences. Improved energy management may commence in the operating theatre and intensive care unit but must ultimately encompass the whole hospital as a significant source of CO2 emissions. Numerous measures can already be implemented today, and appropriate steps should be taken at a local level. Last but not least, the importance of research and teaching is emphasized as a key factor in successfully successfully facing the challenge of ecological sustainability in anaesthesiology and intensive care medicine.
Gesehen am 25.09.2020